Parental marital conflict and adolescent anxiety: The moderating roles of physical activity and gender. - Yan, Chuqi; Liu, Yang; Xiao, Ting; Pan, Mengting; Zhang, Tiancheng; He, Ziling; Gan, Yan (Psychology & Psychotherapy: Theory, Research & Practice, 2026)
Objective: This cross‐sectional study examined the impact of parental marital conflict on adolescent anxiety and the moderating roles of physical activity and gender, with additional gender‐stratified analyses to test differences between boys and girls. Methods: A total of 3974 adolescents participated in this study. Standardized questionnaires assessed perceived parental marital conflict, anxiety symptoms and physical activity behaviours. Stepwise regression analyses were conducted using SPSS to examine associations among parental marital conflict, anxiety, physical activity and gender. Results: The findings revealed that parental marital conflict was positively associated with adolescent anxiety (r =.344, p <.001) and negatively associated with physical activity (r = −.047, p <.01), while physical activity was inversely related to anxiety (r = −.087, p <.001). Moderation analyses showed that physical activity exerted a significant buffering effect on the relationship between parental marital conflict and anxiety (β = −.040, p <.01). Gender also moderated this association (β =.045, p <.01), with girls being more vulnerable to anxiety under parental marital conflict. Gender‐stratified analyses indicated that the buffering effect of physical activity was more pronounced among boys than girls. Conclusion: This study suggested that physical activity may support the alleviation of adolescent anxiety related to parental marital conflict; however, its effects are limited and subject to individual differences. Accordingly, interventions should not rely solely on physical activity but adopt more comprehensive strategies that consider gender differences and psychological vulnerability to promote adolescents' mental health under family stress.